2012
DOI: 10.1136/heartjnl-2012-302346
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance measurement of myocardial extracellular volume in health and disease

Abstract: Myocardial ECV, assessed non-invasively in the septum with equilibrium contrast cardiovascular magnetic resonance, shows gender differences in normal individuals and disease-specific variability. Therefore, ECV shows early potential to be a useful biomarker in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
182
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(218 citation statements)
references
References 38 publications
24
182
4
8
Order By: Relevance
“…Furthermore, Thompson et al showed that reduced non-contrast myocardial T1 values are the most sensitive and specific cardiovascular MRI parameter in patients with AFD irrespective of sex and LV morphology and function [71]. ECV in AFD is normal compared to healthy volunteers whereas ECV is higher in other diseases [72].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…Furthermore, Thompson et al showed that reduced non-contrast myocardial T1 values are the most sensitive and specific cardiovascular MRI parameter in patients with AFD irrespective of sex and LV morphology and function [71]. ECV in AFD is normal compared to healthy volunteers whereas ECV is higher in other diseases [72].…”
Section: Anderson Fabry Disease (Afd)mentioning
confidence: 99%
“…[15][16][17][18][19] CMR impacts a variety of clinical management issues ranging from diagnosis and family screening to procedural planning for septal reduction therapy. 20,25,[38][39][40][41] Newer data demonstrate that extensive LGE, occupying ≥15 % LV myocardium, identifies patients at an increased sudden death risk and these patients may ultimately benefit from ICD placement for primary prevention. 2,15 These observations help to justify an expanded role of CMR in the routine assessment of patients with HCM.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Although CMR findings may be suggestive of a phenocopy in a patient undergoing evaluation for HCM, CMR findings in themselves are not diagnostic and must be considered within the clinical contest of an individual patient.…”
Section: Infiltrative Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Diagnostic tools such as ECG and echocardiography remain fundamental to diagnosis and treatment of HCM but cardiac MRI (CMR) improves diagnostic accuracy and provides additional phenotypic information in patients with established disease (Figure 2). [4][5][6][7] For example, in one study, CMR identified hypertrophy in about 10% of sarcomere mutation carriers thought to have normal wall thickness by echocardiography. 8 Novel CMR sequences, such as T1 mapping, provide quantitative estimates of the myocardial extracellular volume (ECV) (and therefore a surrogate measure of interstitial fibrosis) 5 and, in one study, an increase in ECV was reported in individuals with sarcomere mutations but without LV hypertrophy.…”
Section: Hypertrophic Cardiomyopathy Cardiac Imaging and Circulating mentioning
confidence: 99%